Women Breaking the Barrier in Technology Startups Through an Innovative Business Model: A Case Study of Sree Technologies - Naredla, Suman; Ramesh Babu, D (International Journal of Engineering and Technology, 2018)
Entrepreneurship is becoming critical to the success of any country. Women entrepreneurs are playing an important role. Studies have shown the problems faced by women entrepreneurs. This paper focuses on how two entrepreneurs overcome the challenges by finding a right business model. The paper provides the details of their background, the company information, and their story so that it can help other entrepreneurs and can be used as a case in engineering or business courses. The purpose of this paper is to focus on how two entrepreneurs overcome the challenges by finding a right business model. The methodology we used is the case study approach and study was conducted in Telangana. Data collection is primary, as we have collected through personal interviews technique.  This paper came out with exceptional findings like., a right business model can help to overcome the capital and networking problems faced by women entrepreneurs, a right mix of focus and breadth of services is necessary for success. The findings evolved from the study may not be suitable for majority of the startups, as the study is not on generic problems of startups and study was conducted on only one sample of startup, as it is a case based study.   The work is an outcome of one to one discussion (face to face interview) with the co-founders on regular basis to understand the culture of startups in India and the problems faced by them in particular. This study will help other entrepreneurs and can be used as a case in engineering or business courses.